Pre-service Education and Performances in Teacher Licensure Examination among Graduates of Mindoro State College of Agriculture and Technology - Arenillo, Sonia A.; Arenillo, Medel T. (JPAIR Multidisciplinary Research, 2009)
Performance in Licensure Examination for Teachers provides an index of the quality of teacher education program offered by the different teacher training institutions. Using descriptive-correlational and comparative surveys, data were gathered from sixty-five respondents who graduated in various fields of specialization through record analysis. Results indicated that respondents manifested better performance in pre-service education compared to their performance in LET. Analysis of data further showed that the performance in pre-service education of respondents was significantly correlated with their performance in LET in terms of general education and professional education. However, performance in subject specialization was found insignificant. Comparative analysis between male and female respondents' performance in pre-service education revealed that different respondent groups were at par level in professional education and subject specialization. The indicative difference was prominent in general education. The performance in subject specialization differed significantly with the two groups.
Keywords: teachers board performance; preservice education